Factor analysis evaluation of Schein’s career orientations inventory in Colombia - Cortés Sánchez, Julián David; Grueso Hinestroza, Merlin Patricia (Business: Theory and Practice, 2017)
The Career Orientation Inventory model proposed by Edgar Schein is one of the most discussed methods for identifying individuals’ career orientations. However, there are several gaps related to its implementation for developing countries using factor analysis and digital open access data. We conducted exploratory and confirmatory factor analysis for a sample of 116 employees of a contact center in Colombia to test whether there were significant differences among career anchors (CAs) and gender, educational attainment, or age. The results show: a different number of factors from those proposed by Schein; variances in security/stability and managerial competence CAs concerning gender and educational attainment; and lifestyle is not the dominating CA in women.